Content validation through expert judgement of web-based megalithic culture visualization - Sri Yanti Mahadzir; Zurina Muda; Siti Aishah Hanawi; Zuliskandar Ramli (Penerbit Universiti Kebangsaan Malaysia, 2024)
The lack of information disclosure and weaknesses in delivering information related to megalithic treasures in Malaysia, especially in Negeri Sembilan, limit the sharing of information about this tradition and culture with the general public. It also means that this megalithic heritage is, to some extent, increasingly forgotten by the current generation. This study was conducted after developing the Negeri Sembilan megalithic web application. In this light, the accuracy, appropriateness, and validity of any information should be verified before sharing it with other parties. Therefore, this study aimed to validate information contents based on the expert judgement of the web-based visualization of megalithic culture information for Negeri Sembilan. Accordingly, content validation was conducted with 7 experts in related fields. The data obtained were analyzed using the Statistical Package for Social Science (SPSS). Overall, the results of the content validity assessment in this study have successfully demonstrated that all seven experts provided a high interpretation assessment score with an average mean (M) of 4.61. The experts have agreed that the web application is suitable and ready to be shared with users and the public in its current state because the quality of the web application is very satisfactory. In addition, this analysis proves that the Negeri Sembilan megalithic web application meets the criteria for content validity as assessed by experts. Therefore, this indirectly validates the ability of the web application to convey valid information contents.